Isolation and Identification of Gram Negative Bacteria in The Lumen Fluid of Colorectal Cancer Patients - Rita Maliza; Hevi Horiza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Colorectal cancer is one of the major health problems in Indonesia and the third most common cause of death worldwide. Colorectal cancer is a cancer of the colon and the rectum. There is considerable research evidence demonstrating the important role of complex gut microbiota communities in developing intestinal tumorigenesis. This study aims to isolate and identify gram-negative bacteria found in the colonic lumen fluid of colorectal cancer patients using the gram-staining method and biochemical test. From microscopic identification results, macroscopic gram staining, motility test, Simon citrates agar (SCA), and triple sugar iron agar (TSIA) tests against H1 and H2 isolates described gram-negative stem bacteria included in the Enterobacteriaceae family belonging to the species Shigella sp.